Healthcare Social Workers’ Work in Somatic Hospital Care: Organizational Conditions, Professional Role, and Integration in Healthcare Teams - Ståhl,Daniel (2026)
This study aimed to examine how healthcare social workers perceived organizational conditions and how these influenced their working conditions, professional role, and integration within healthcare teams in somatic hospital care. The study was based on a qualitative research design and involved six semi-structured interviews with healthcare social workers working in somatic hospital settings. The empirical material was analysed using an inductive thematic approach. The findings showed that organizational conditions were experienced as central in shaping healthcare social workers’ everyday professional practice. Working conditions were closely linked to leadership structures, organizational placement, access to collegial support, and the degree of clarity regarding roles and responsibilities. The professional role was described as highly autonomous but also as carrying extensive individual responsibility, often requiring healthcare social workers to negotiate boundaries and priorities in the absence of clearly defined organizational frameworks. Integration within healthcare teams was found to be dependent on both organizational arrangements and relational practices, such as physical proximity, participation in team routines, and ongoing efforts to maintain visibility and professional legitimacy. Overall, the study demonstrated that organizational conditions influenced healthcare social workers’ professional practice through how they were interpreted and managed in everyday work, rather than as fixed structural determinants.
Keywords: healthcare social workers; organizational conditions; professional role; interprofessional collaboration; somatic hospital care